Barriers to providing spiritual care from a nurses' perspective: A content analysis study - Ghodratollah Momeni; Maryam Sadat Hashemi; Zeinab Hemati (Wolters Kluwer Medknow Publications, 2022)
Background: Spirituality is an important dimension of holistic nursing, and spiritual care is essential to ensure the achievement of optimal care in nursing profession. The aim of this study was to explain the obstacles to providing spiritual care from the perspective of nurses. Materials and Methods: The present qualitative study was conducted between November 2020 and June 2021 with a content analysis approach. Participants included 30 nurses, selected through purposive sampling, working in the general wards and intensive care units of Isfahan University hospitals. Data collection method was semi-structured personal interviews. After recording and transcription word by word, all data were analyzed through qualitative content analysis. MAXQDA 11 was used for data analysis.Results: Research findings included 323 primary codes and two main categories "individual barriers and organizational barriers" and eight subcategories "non-compliance with human resources standards, lack of attention of organizational managers to the importance of holistic care, motivational barriers, training barriers, barriers to interprofessional collaboration, environmental barriers, barriers related to the nurses, and communication barriers."Conclusions: Using the results of the study, policymakers and nursing managers will be able to help facilitate spiritual care, and ultimately, improve the quality of nursing care by improving the infrastructure and removing existing barriers.